Literatura e infância: entre filosofia, história e “despropósitos” - Márcia Cabral da Silva (Estudos de Literatura Brasileira Contemporânea)
In this paper we emphasize some reflections in the context of the relationship among literature, childhood and experience. Specifically, the aim is to think about the philosophical dimension of language in dialogue with contemporary literary works that foc us on childhood. On one hand, we reflect on the relationship between fiction and childhood, with special emphasis on the books that have children as main characters that have an ability to see the reality from another perspective , to philosophize. On the o ther hand, we emphasize the examination of literary strategies capable of causing perplexity in relation to the descriptive and communicative character of everyday language. In order to develop the study, the focus is on the following works: Exercícios de ser criança (1999) and Memórias inventadas: a infância (2003), by Manoel de Barros.